Columnar to Equiaxed Transition in 316 L Stainless Steel - Alicia E. Ares (The Minerals, Metals and Materials Society, 2002)
316 L Stainless Steel samples were solidified directionally under conditions which produced the columnar to equiaxed transition. The position of the transition was located in each sample and the distance from the bottom of the ingot was measured. During solidification the distribution of temperatures were measured by means of thermocouples located strategically. From the measured temperatures the following parameters were derived; the local temperature gradient, the cooling rate and the velocities of the liquid and solidus fronts. Comparing the location of the transition and the values of these parameters it was found that the temperature gradient reaches negative values of as low as -13.44 "C/cm, and velocities of the fronts of around 0.1 cm/s. Also, a supercooling of 5.81°C were measured which was associated with the supercooling for the nucleation and growth of the equiaxed grains ahead of the columnar front. In addition the primary and secondary dendritic spacing was measured in both regions. The spacing was compared with the predictions from available models. The results are presented and discussed in the frame of the results obtained for other alloys